Pattern of anorectal malformation in a tertiary care hospital of Bihar - Hasan, Zaheer; Thakur, Vinit Kumar; Yadav, Ramdhani; Chaubey, Digamber (International Surgery Journal, 2020)
Background: Anorectal malformation (ARM) is common cause of neonatal intestinal obstruction and is one of the most common neonatal surgical emergency encountered by paediatric surgeons. There is no published study about the prevalence of ARM cases within the referral zone of the hospital. This study was done to demonstrate the burden of Anorectal malformation and their surgical intervention as seen in Indira Gandhi Institute of medical science, Patna, Bihar. Methods: Data were retrospectively collected over a period of four years between January 2015 and December 2018. The data collected were demographic status of the patient, diagnosis, associated anomaly, duration of hospital stay and their surgical intervention. Results: There were 395 cases of anorectal malformation out of 93203 OPD patients (0.42%). Male to female ratio of 3.01:1. ARM also represented 25.3% of neonatal emergency surgical procedures. The majority of the patient had presented in the neonatal period (51.6%) with mean weight of 2.6 kg. The most common type of ARM found in male patient was rectourethral fistula n=215 (54.4%) in which 164 (76.2%) patients were with rectobulbar fistula and 51 (23.8%) patients had rectoprostatic fistula. Sixty nine (17.4%) female patients presented with perineal fistula. Conclusions: We found a clear male preponderance of anorectal malformation in our study. Patients affected were mostly from poor socioeconomic strata of the society. Present study confirms huge work load of anorectal malformation in this region. This will be helpful in future planning and effective management including financial constraints of the treatment for our poor patients.